The Approach of Imām Al-Biqāʻī in Determining the Objectives of the Quranic Chapters - Misnawati, Misnawati; Elatrash, Radwan Jamal (Al-Jami'ah Research Centre, 2023)
Imam al-Biqāʻī is one of the most prominent Quranic commentators who took care of the objectives of Quranic chapters and became the first scholar to draw attention to this science. Benefited from the science of the Quranic munāsabah, al-Biqāʻī analysed the objectives of the Quranic chapters in his books Naẓm al-Durar fī Tanāsub al-Āyāt wa al-Suwar and Maѕāʻid al-Naẓr li al-Ishrāf ‘alā Maqāѕīd al-Suwar. Therefore, the nature of this paper requires that the researchers rely on the inductive method to reach the views of scholars and Quranic commentators, especially that of al-Biqāʻī on the topic, to prove the approach of al-Biqāʻī in the purposes of the sūrah. The authors argue that relying on the sciences of the Quranic tanāsub and siyāq, al-Biqāʻī concluded that revealing monotheism is the ultimate goal of most of the Quranic chapters.[Imam al-Biqāʻī salah satu tokoh tafsir terpenting yang berkontribusi dalam Ilmu Maqāṣid ṣ al-Suwar al-Qur’āniyyah, bahkan beliau di garda terdepan dalam ilmu ini sebagai perintisnya. Dengan mendalami ilmu Munāsabah al-Quran, beliau menganalisis dan menentukan tujuan surat-surat al-Qur’an sebagaimana tergambar dalam kitabnya yang berjudul Naẓm al-Durar fī Tanāsub al-Āyāt wa al-Suwar dan Maṣāʻid al-Naẓr li al-Ishrāf ʻalā Maqāṣid al-Suwar. Artikel ini menggunakan pendekatan induktif untuk mengumpulkan pendapat para ulama dan para ahli tafsir, khususnya pendapat al-Biqāʻī, terkait disiplin ilmu tersebut untuk menelisik karakteristik pendekatan al-Biqāʻī dalam menentukan tujuan dari surat al-Quran. Kesimpulan dalam penelitian ini adalah bahwa menurut al-Biqāʻī, tauhid adalah tujuan tertinggi di sebagian besar surat al-Quran. Pandangan al-Biqāʻī ini dia dapatkan melalui dua ilmu yang menjadi referensinya, yaitu ilmu al-Tanāsub dan al-Siyāq].